A mechanistic insight into benefits of aggregation induced emissive luminogens in cancer. (3rd July 2021) - Kumari, Rashmi; Sunil, Dhanya
Abstract: Exploration of advanced chemotheranostics that benefit from a combined in vivo strategy of cancer diagnosis and chemotherapy simultaneously is highly valued and will expose novel possibilities in modifying treatment and reduce side effects. In recent years, nanodrug delivery systems that incorporate aggregation-induced emissive luminogens (AIEgens) have been developed to track and monitor anticancer drug release, trace translocation processes and predict chemotherapeutic responses. There are several classes of AIEgen based chemotheranostics such us stimuli-responsive nanoprodrugs, pH-sensitive mesoporous silica nanocarriers, supramolecular polymer systems, drug encapsulated carriers, carrier-free nanodrugs, self-indicating drug delivery nanomachines and AIEgen-prodrug co-assembly. The present review conveys mechanistic insight into the benefits of AIEgens in the theranostic application by illustrating the recent breakthroughs in chemotheranostic nanomedicines that incorporate these unique fluorophores as signal reporters. The perspectives that can be further explored are also highlighted with the hope to instil more research interest in the advancement of AIE active cancer chemotheranostics for imaging and treatment in vivo . HIGHLIGHTS: Aggregation induced emissive materials (AIEgens) exhibit unique advantages over conventional luminogens for synergistic diagnosis and chemotherapy of cancer in vivo . The combination of AIE and nanotechnology offers an excellent platform to fabricate advanced chemotheranostics for cancer therapy.